Pengendalian Kualitas Dengan Menggunakan Metode Seven Tools Untuk Meningkatkan Produktivitas Di PT Jogjatex - Wahyu Hadi Sutiyono; Annisa Fitria; Hilman Adiatma; Widya Setiafindari (Jurnal Sains dan Teknologi, 2023)
This study aims to determine quality control at PT. JOGJATEX, find out the factors that cause product defects, find out what are the main problems that cause product damage. and provide solutions to reduce the level of product defects. PT JOGJATEX which is engaged in textile knitting. The method used in this study is the Seven Tool Seven tools method is a graphical method used to solve problems in the field of production, especially problems related to quality (Quality). These seven tools or seven basic tools were discovered and introduced for the first time by Kaoru Ishikawa in 1968 who was a figure of quality management innovation in Japan. The conclusion of this study is regarding the production defect report at the Jogjatex company. This product defect is affected by internal and external influences. These factors are basically influenced by several factors including temperature, human resources and machines. The solution taken to overcome the problem in this research is to design a room temperature detector, namely the DS18B20 Temperature Sensor.